Major element glass data of marine tephras from sediment core M141/1_1176-1 - Julie Belo (PANGAEA, 2025)
A total of 44 gravity cores were collected in the Azores region in 2017, during the R/V Meteor cruise M141/1. Based on their length, content in tephra layers, and spatial distribution around São Miguel, 22 cores have been carefully selected as the most representative to gain insights on the volcanic history and the depositional marine environment around the islands of the eastern group of the archipelago. In total, 454 samples from 350 ash- or pumice/scoria/lapilli- bearing horizons were examined. Here we present the major element glass data of the Pleistocene to Holocene marine tephra record around the eastern islands of the Azores. Marine lapilli samples were cleaned in an ultrasonic bath and then crushed. All ash samples and the previously crushed lapilli samples were wet-sieved into different grain size fractions. The 125-63 microns fraction was embedded with epoxy in pre-drilled acrylic mounts and polished for geochemical micro-analyses. Major and minor element compositions of glass shards were conducted using a JEOL JXA 8200 wavelength dispersive EMP at GEOMAR Helmholtz-Centre for Ocean Research, Kiel, Germany. Every 60 individual glass shards analyses were bracketed by a set of four standard analyses. We analyzed 15–25 single glass shards per sample (~7,000 analyses in total). Outliers with totals below 92 wt.%, as well as accidental mineral analyses were removed from the dataset.
In: Belo, J (2025): Major element glass data of marine tephras around São Miguel Island, Azores [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.986779